1998
DOI: 10.1002/(sici)1521-3935(19980401)199:4<641::aid-macp641>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Ordering kinetics of cylindrical and spherical microdomains in an SIS block copolymer by synchrotron SAXS and rheology

Abstract: The ordering kinetics of cylindrical and spherical microdomains in a polystyrene-block-polyisoprene-block-polystyrene (SIS) copolymer were studied using synchrotron small-angle X-ray scattering (SAXS) and rheology upon quenching the sample from a disordered state to an ordered state having either spherical or cylindrical microdomains. The SIS exhibits an order to order transition at -181 "C, a lattice disordering transition at -21OOC and becomes disordered at higher temperatures. Higher order peaks in the SAXS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 36 publications
9
61
1
Order By: Relevance
“…The SAXS signal of PS 7 ‐ b ‐PEO 136 ‐ b ‐PS 7 showed a principal reflection and smaller peaks located at relative q ‐values √2:√3:2, with respect to the main peak. This sequence can be attributed to a phase separated morphology, where spheres of PS are arranged according to a body centered cubic lattice . As the volume fraction of PEO was decreased in PS 68 ‐ b ‐PEO 136 ‐ b ‐PS 68 , the polymer presented only one reflection, indicating that PS and PEO tend to segregate in domains which, in average, are 12 nm apart.…”
Section: Resultsmentioning
confidence: 99%
“…The SAXS signal of PS 7 ‐ b ‐PEO 136 ‐ b ‐PS 7 showed a principal reflection and smaller peaks located at relative q ‐values √2:√3:2, with respect to the main peak. This sequence can be attributed to a phase separated morphology, where spheres of PS are arranged according to a body centered cubic lattice . As the volume fraction of PEO was decreased in PS 68 ‐ b ‐PEO 136 ‐ b ‐PS 68 , the polymer presented only one reflection, indicating that PS and PEO tend to segregate in domains which, in average, are 12 nm apart.…”
Section: Resultsmentioning
confidence: 99%
“…We thus found that the disordering of morphology in the neat sample was probably due to mixed effects of ODT and the thermal decomposition. Generally, it is known that the D of a micro‐phase separated structure formed by a block copolymer decreases with increasing temperatures, especially above ODT, since the segregation power between components decreases . On the other hand, it is seen in Figure b that the D of the neat sample started to increase at 170 °C and further increased with a higher slope at temperature higher than 200 °C, which is opposite to the expectation.…”
Section: Figurementioning
confidence: 65%
“…Since B is positive in most case, χ decreases with an increase in temperatures. When the temperature reaches certain level, order‐disorder transition (ODT) or order‐order transition (OOT) can be caused for the block copolymers with a moderate segregation power . In other cases, if the segregation power between components is specifically high, the thermal decomposition of chains occurs before ODT or OOT in the course of the temperature increase.…”
Section: Figurementioning
confidence: 99%
“…Because of the incompatibility between these two blocks, with the change of chemical composition of two blocks, SBC generally forms various ordered phase morphologies, such as spherical, cylindrical, and lamellar morphologies . In addition, the phase morphology of SBC can also be obviously changed by different processing conditions and thermal history …”
Section: Introductionmentioning
confidence: 99%